Simulasi Sistem Antrian pada SPBU 14.236.100 Menggunakan Promodel - Mukhlizar, Mukhlizar (Jurnal Optimalisasi, 2016)
Has done a simulation for system queues at gas stations with observation for 3 hours. From the calculation of the data, obtained the arrival rate of 115 customers per hour and service levels for three fueling facilities as 140.48%. By performing simulation using ProModel software, obtained total customer arrival as 540 customers over 3 hours of simulation. With a utilization rate of 7.17% for the first facility; 6.42% for the second facility and 5.48% for the third facility. The average time of arrival at the first facility is for 0.9 minutes, a second facility for 0.6 minutes and the third facility for 0.4 minutes.Keywords: Simulation, Utilization, Queue System.